2007
DOI: 10.1021/la063130f
|View full text |Cite
|
Sign up to set email alerts
|

Condensation and Wetting Transitions on Microstructured Ultrahydrophobic Surfaces

Abstract: On rough surfaces, two distinct wetting modes can appear. These two states are usually described by the theories of Cassie (drops suspended on top of roughness features) and Wenzel (drops impaled on roughness features). Whereas the wetting transition from the Cassie to the Wenzel state has been relatively well studied both experimentally and theoretically, the question of whether metastable Wenzel drops exist and how they transition to the Cassie state has remained open. In this work, we study the wetting beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
208
3
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(228 citation statements)
references
References 42 publications
(52 reference statements)
15
208
3
2
Order By: Relevance
“…On many surfaces this energy barrier is large enough that a drop of water will tend to stay in the state that it is put in (the Cassie-Baxter bridging state for a drop applied from the top) unless forced into the other state. A condensing liquid will always form in contact with the surface so droplets forming this way often begin in the Wenzel state and can be trapped there by the energy barrier in the same way that droplets deposited gently onto the surface will start in the Cassie-Baxter state [44]. The way that water condenses on superhydrophobic materials is of particular interest, because of its potential use in condensers [45,46].…”
Section: Bridging-to-penetrating Transitionmentioning
confidence: 99%
“…On many surfaces this energy barrier is large enough that a drop of water will tend to stay in the state that it is put in (the Cassie-Baxter bridging state for a drop applied from the top) unless forced into the other state. A condensing liquid will always form in contact with the surface so droplets forming this way often begin in the Wenzel state and can be trapped there by the energy barrier in the same way that droplets deposited gently onto the surface will start in the Cassie-Baxter state [44]. The way that water condenses on superhydrophobic materials is of particular interest, because of its potential use in condensers [45,46].…”
Section: Bridging-to-penetrating Transitionmentioning
confidence: 99%
“…In contrast, and although this process is of major importance for the evaluation of corrosion, the studies of condensation-induced wetting on superhydrophobic surface and their corresponding wetting properties (self-cleanliness, different wetting states), are much less documented [18][19][20][21][22][23][24][25][26][27][28][29]. The aim of the present work is thus to study condensation of water on a multiscale rough superhydrophobic surface where the contact angle is varied in a wide range (70-150 • ).…”
Section: Introductionmentioning
confidence: 99%
“…Different from traditional superhydrophobic surfaces, which are characterized by the bouncing or rolling off of deposited millimeter-size large drops, [32,33] CMDSP surfaces support the self-removal capability of smallscale condensate microdrops. It has been reported that classical superhydrophobic lotus leaves (Figure 1a), [34][35][36][37] as well as artificial surfaces consisting of hierarchical micro-and nanostructures, [38] one-tier microstructures, [39][40][41][42][43] or nanostructures [44,45] with larger characteristic interspaces, present a low-adhesivity property to the deposited water macrodrops, but become highly adhesive to condensed microdrops (Figure 1b). This is because moisture easily penetrates the microscale valleys or cavities.…”
mentioning
confidence: 99%